Relationship Between Dental Caries And Children’s Nutritional Status Elementary School In North Tanimbar District, Tanimbar Islands - Herman (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Background: Dental caries is a disease in the oral cavity that occurs due to the interaction of bacteria that convert carbohydrates in food debris into acids through the fermentation process. In school children, dental caries is an important problem because it causes pain complaints, spreads infection to other parts of the body, resulting in decreased productivity. Stunting is a condition that affects the growth and development of children, caused by long-term malnutrition, so it is a National Priority Program. This study aims to analyze the relationship between dental caries and nutritional status in primary school children in North Tanimbar District, Tanimbar Islands. Methods: Analytical observational research with a cross-sectional design, using the simple random sampling method in 16 elementary schools in North Tanimbar District in February-March 2024, with a sample of 328 children. Determination of nutritional status based on anthropometric measurements of nutritional status (length-for-age and BMI-for-age). Dental caries examination is done by looking at teeth that have caries or not. Results: 124 (37.8%) children had dental caries and had stunting nutritional status, 17 (5.2%) children did not have dental caries and had stunting nutritional status. Chi-square test results of dental caries and stunting nutritional status, p value = 0.000. 78 (23.8%) children had dental caries and had an thinnes nutritional status, 7 (2.1%) children did not have dental caries and had an thinnes nutritional status. Chi-square test results of dental caries and thinnes nutritional status, p value = 0.000. Conclusion: There is a relationship between dental caries and nutritional status in elementary schools children in North Tanimbar District.